Managing academic rights, duties and accountability from tawhidic paradigm - Mhd. Sarif, Suhaimi; Ismail, Yusof (World Academy of Islamic Management, 2017)
This paper explores the critical importance of Tawhidic paradigm for academic rights, duties and accountability. In the recent years, academic rights, duties, and accountability (RDA)have been ‘aligned’ with the commercial objectives of tertiary education. Education has been transformed into a commodity. From Tawhidic paradigm, education is a Divine mechanism to mold and shape thinking, feeling and behaviour of people. The study provides conceptual aspects of the Tawhidic paradigm (Islamic monotheism) and links the spirit of Tawhid (monotheism) with academic rights, duties and accountability and then they are integrated with the ethos of Tawhid which balancing the gain in the worldly life and the pleasure in the Hereafter. The study obtained the views of 10 selected representatives of academic staff association that participated in various meetings at the Malaysian Academic Associations Council (MAAC) between 2010-2016 pertaining to academic rights, duties and accountability from the current practices and the way forward from their religious and spirituality perspectives. The results of the study showed that the academic rights, duties and accountability (RDA) are compromised by higher education providers for commercial gain,survival and sustainability. While commercial advantage is necessary for the higher education to be competitive, they should not compromise the need to nurture and educate people with religiosity and spirituality rituals and practices. The study has immediate implications for enhancing personal and professional values of academic movement to be sustainable. However, the results of the qualitative study have to be read within the context and they are not to be generalised. The future studies should use case study and personal interview with all the stakeholders of academic institutions in Malaysia.